ROUNDTABLE TECHNIQUE AND STUDENTS' WRITING ABILITY - Amalia, Shynta (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2021)
In spite of its importance, writing seems always be a challenging skill for students to master in learning English. Persuading the teachers to persistently try different teaching techniques to reach the goal of teaching better writing is a must. Using roundtable technique become one of the choices. As this experimental study has proven that using roundtable technique give significant effect on the students’ writing ability. Toward the 42 students taken as the sample of the research, it is proved that there was significant difference on the students’ writing ability before (M=54.48, SD=13.155) and after being taught by using roundtable technique (M=73.9, SD=7.569), t(20)=13.55, P<0.0005. The results of independent sample t-test also shows that there is significant difference in writing ability between the students taught by using roundtable technique (M=73.9, SD=7.569) and those who were not (M=64.86, SD= 15.32), t(29)=2.426, P<0.05